2003
DOI: 10.1152/japplphysiol.00310.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid saline infusion on lung mechanics and airway responsiveness in humans

Abstract: . Effects of rapid saline infusion on lung mechanics and airway responsiveness in humans. J Appl Physiol 95: 728-734, 2003. First published May 2, 2003 10.1152/japplphysiol.00310.2003.-Lung mechanics and airway responsiveness to methacholine (MCh) were studied in seven volunteers before and after a 20-min intravenous infusion of saline. Data were compared with those of a time point-matched control study. The following parameters were measured: 1-s forced expiratory volume, forced vital capacity, flows at 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 29 publications
(38 reference statements)
9
38
0
Order By: Relevance
“…However, forced vital capacity decreased by 4.7%, but this change did not reach the level of statistical significance (p=0.09). Reduced expiratory flows were also evident following intravenous saline infusion in a previous study by our group and other previous studies (Cutillo, 1995;Pellegrino et al, 2003;Robertson et al, 2004), without any significant change in diffusing capacity of the lung (Robertson et al, 2004), suggesting the presence of peribronchial cuffing without significant fluid accumulation in the alveoli. Expiratory flow returned almost to baseline values after recovery measurements were acquired, suggesting that any peribronchial cuffing resulting from infusion was no longer significantly obstructing airways.…”
Section: Changes In Pulmonary Function and Impedance Cardiography Measupporting
confidence: 78%
“…However, forced vital capacity decreased by 4.7%, but this change did not reach the level of statistical significance (p=0.09). Reduced expiratory flows were also evident following intravenous saline infusion in a previous study by our group and other previous studies (Cutillo, 1995;Pellegrino et al, 2003;Robertson et al, 2004), without any significant change in diffusing capacity of the lung (Robertson et al, 2004), suggesting the presence of peribronchial cuffing without significant fluid accumulation in the alveoli. Expiratory flow returned almost to baseline values after recovery measurements were acquired, suggesting that any peribronchial cuffing resulting from infusion was no longer significantly obstructing airways.…”
Section: Changes In Pulmonary Function and Impedance Cardiography Measupporting
confidence: 78%
“…Indeed, the case-control difference suggests increased bronchial wall hysteresis, and therefore smooth muscle contraction, as mechanism to the EIB. Healthy children may exhibit small degree of airway narrowing after exercise not associated with dilatory effect of DI, and the mechanism put forward was transient hyperemia in the airway wall (17) based on the experimental report that rapid fluid loading of the latter promotes airway narrowing insensitive to DI (42).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the large subatmospheric pressures during deep inspiration may lead to extravasation of fluid in the inflamed asthmatic airway wall, thereby enhancing airway wall thickness. However, two studies using fast intravenous infusion of saline, resulting in airway wall thickening by edema and fluid flux (9,11), showed no effect on deep inspiration-induced bronchodilation (37).…”
mentioning
confidence: 99%